Kepuasan Kerja Dan Dampaknya Terhadap Profesionalisme Guru - Fiska Ilyasir (LITERASI (Jurnal Ilmu Pendidikan), 2013)
This article attempts to discuss the impact of job satisfaction of teachers in Indonesia to their performance as professional educators. There are several factors that affect their satisfaction of the teacher. Psychological factor, which is related to mental and attitudes, including interest, talent, and skills; Social factor, that related to their social interaction with superiors, colleagues, students, and community. Physical factors, the factor related to the condition of the school such as policies that applied, type of work, working time, school facilities, teaching equipment facilities, teacher's office. teacher physical conditions like health, age, and so on. Financial factors that associated with security and welfare, including sallary, social security, work promotion, and so on. All of these factors certainly can not be changed only by the teacher, but they also need help from external parties, both government and society. Keyword: Professional Educators